The environmental legacy of the Ixtoc-I oil spill in Campeche Sound, southwestern Gulf of Mexico - Soto, Luis A.; Botello, Alfonso V.; Licea-Durán, Sergio; Lizárraga-Partida, Marcial L.; Yáñez-Arancibia, Alejandro (Frontiers in Marine Science, 2014)
The southwestern Gulf of Mexico constitutes an important subsystem within a Large Marine Ecosystem. Due to its high biodiversity, living resources and energy resources, this region is strategic in the national plans for social and economic development of Mexico. The discovery of fossil fuel reserves in the seabed of Campeche Sound in the 1970s promoted the rapid expansion of the national oil industry in offshore waters. Unfortunately, the accidental blowout of the most productive well (Ixtoc-I) in June of 1979, caused the first–world massive oil spill in a tropical marine environment. More than 3.4 million of barrels of crude oil were liberated in an ecosystem formerly renowned for its pristine conditions. In the aftermath of this dreadful accident, an immediate concern emerged not only for the oil acute effects but also for the long-term environmental consequences derived from the residual hydrocarbon compounds accumulated in coastal environments of the southern Gulf of Mexico. The attempts to assess the magnitude of the environmental damage were strongly precluded by the lack of pre-spill information. Natural variability in the ecosystem and oil weathering-factors contributed to attenuate the acute pollution effects that lasted nine months. However, the post-spill environmental alterations caused by the Ixtoc-I blowout still remain unanswered. The sinking of the Deepwater Horizon oil platform in the deep-waters of the northern Gulf of Mexico, in 2010 rekindled our concern for the great risk involved for human lives and the health of shallow and deep sea habitats. The authors of this contribution offer their views on this environmental riddle from their own perspective as direct witnesses of the Ixtoc-I environmental tragedy.